2013
DOI: 10.1007/s00535-013-0764-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying narrow-band imaging of surface maturation in early differentiated-type gastric cancers after Helicobacter pylori eradication

Abstract: Identification of surface maturation under NBI-ME offers a promising approach for accurate diagnosis of early gastric cancers after successful eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 32 publications
7
118
0
Order By: Relevance
“…All EGC lesions were histologically diagnosed as differentiated adenocarcinoma. Distinct histologic changes of gastric cancer after H. pylori eradication are characterized as either regenerating non-tumorous epithelium covering over the tumorous tissue and/or surface differentiation of tumors [8][9][10], which may influence the endoscopic or histological diagnosis using the endoscopic biopsy. We investigated these histopathological characteristics in the EGC lesions.…”
Section: Histological Assessment Of Resected Specimensmentioning
confidence: 99%
See 3 more Smart Citations
“…All EGC lesions were histologically diagnosed as differentiated adenocarcinoma. Distinct histologic changes of gastric cancer after H. pylori eradication are characterized as either regenerating non-tumorous epithelium covering over the tumorous tissue and/or surface differentiation of tumors [8][9][10], which may influence the endoscopic or histological diagnosis using the endoscopic biopsy. We investigated these histopathological characteristics in the EGC lesions.…”
Section: Histological Assessment Of Resected Specimensmentioning
confidence: 99%
“…Location, morphology, color and depth and unexpected SM2 case were using Chi statistics. such as regenerating non-tumorous epithelium covering over the tumorous tissue and/or surface differentiation of tumors [9,10], which may confuse the endoscopic diagnosis. We investigated the association between indistinct cases of EGC lesions from the eradication group and the presence of regenerating non-tumorous epithelium and/or surface differentiation of tumors.…”
Section: Diagnostic Reliability Of Wle Ce and Me-nbi For Predicting Egcmentioning
confidence: 99%
See 2 more Smart Citations
“…Hp eradication inhibits formation of intestinal-type cancer, allowing emergence of the gastric type, an additional cause of the difference in morphology between GC with Hp infection and after Hp eradication. Using magnifying endoscopy with narrow-band imaging (NBI) of GC, Kobayashi et al reported that *40 % of differentiatedtype cancers had evidence of gastritis, blurring differentiation of cancer from normal tissues [14]. For post-eradication GC, the lesions are likely to be difficult to detect endoscopically, as they are small, flattened, or depressed in shape, with whitish discoloration.…”
mentioning
confidence: 99%